Paving the way in implementation of SCID newborn screening in developing nations: feasibility study and strategies to move forward in Malaysia - Kumarasamy, Gaayathri; Khairiz, Khayrin; Chang, Wai Leng; Aye, Thin Thin; Ali, Adli (Frontiers in Immunology, 2024)
Early diagnosis and effective management of Primary immunodeficiency diseases (PIDs), particularly severe combined immunodeficiency (SCID), play a crucial role in minimizing associated morbidities and mortality. Newborn screening (NBS) serves as a valuable tool in facilitating these efforts. Timely detection and diagnosis are essential for swiftly implementing isolation measures and ensuring prompt referral for definitive treatment, such as allogeneic hematopoietic stem cell transplantation. The utilization of comprehensive protocols and screening assays, including T cell receptor excision circles (TREC) and kappa-deleting recombination excision circles (KREC), is essential in facilitating early diagnosis of SCID and other PIDs, but their successful application requires clinical expertise and proper implementation strategy. Unfortunately, a notable challenge arises from insufficient funding for the treatment of PIDs. To address these issues, a collaborative approach is imperative, involving advancements in technology, a well-functioning healthcare system, and active engagement from stakeholders. The integration of these elements is essential for overcoming the existing challenges in NBS for PIDs. By fostering synergy between technology providers, healthcare professionals, and governmental stakeholders, we can enhance the efficiency and effectiveness of early diagnosis and intervention, ultimately improving outcomes for individuals with PIDs.